Stability, biomechanics and biocompatibility analysis following different preparation strategies of hierarchical zeolite coatings on titanium alloy surfaces - Liu, Chang; Zhang, Jiaxin; Zhao, Xin; Xu, Mingwei; Liu, He; Zhou, Hongming (Frontiers in Bioengineering and Biotechnology, 2023)
Traditional titanium alloy implant surfaces are inherently smooth and often lack effective osteoinductive properties. To overcome these limitations, coating technologies are frequently employed to enhance the efficiency of bone integration at the implant-host bone interface.Hierarchical zeolites, characterized by their chemical stability, can be applied to 3D-printed porous titanium alloy (pTi) surfaces as coating. The resulting novel implants with a "microporousmesoporous-macroporous" spatial gradient structure can influence the behavior of adjacent cells; thereby, promoting the integration of bone at the implant interface. Consequently, a thorough exploration of various preparation methods is warranted for hierarchical zeolite coatings with respect to biocompatibility, coating stability, and osteogenesis. In this study, we employed three methods: in situ crystal growth, secondary growth, and layer-by-layer (LBL) assembly, to construct hierarchical zeolite coatings on pTi, resulting in the development of a gradient structure. The findings of this investigation unequivocally demonstrated that the LBL-coating method consistently produced coatings characterized by superior uniformity, heightened surface roughness, and increased hydrophilicity, as well as increased biomechanical properties. These advantages considerably amplified cell adhesion, spreading, osteogenic differentiation, and mineralization of MC3T3-E1 cells, presenting superior biological functionality when compared to alternative coating methods. The outcomes of this research provide a solid theoretical basis for the clinical translation of hierarchical zeolite coatings in surface modifications for orthopedic implants.